Design Thinking of Legal Assistance for Sexual Harassment Victims - Dinda Arsi Fitriani; Abdul Wasik (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the inspiration for the hadith of the Prophet. in law enforcement. This research method is qualitative through literature study with a design thinking approach to legal assistance for victims of sexual harassment. The results and discussion of this research include legal justice in society, especially victims of sexual harassment, inspiring the example of the Prophet. in applying the law. This research concludes that the hadith of the Prophet SAW. has inspirational messages in raising awareness in applying fair law through innovative ideas with continuous testing appropriately so that it can be applied to the wider community.